Constraint analysis of cabbage farmers in Khordha district of Odisha, India - Kiran Sourav Das; Bishnupriya Mishra; Abhishek Naik; Rebba Kishore Kumar; Shilpa Bahubalendra; Soubhagya Kumar Sahoo (Environment Conservation Journal)
Horticultural production in India has progressed vividly in recent years, with        vegetable crops, particularly cabbage, showing notable increase in yield and production. Odisha, being among the leading cabbage producing states in the country, has immense potential for growth in this aspect. However, cabbage farmers in Odisha encounter many challenges that restrict their profitability. The present study was  conducted to assess and analyse the constraints faced by cabbage farmers in the Khordha district of Odisha, a region noted for its significant cabbage production.     Ex-post facto research design was used for the study, along with a multi-stage sampling technique. Data were collected from 120 cabbage growers selected randomly, across six villages from Balianta and Balipatna blocks of Khordha district. Responses were collected pertaining to the constraints along a 3-point continuum, and analysed based on their severity using Rank Based Quotient (RBQ) method. They were        categorised into four categories; technical, economic, infrastructural, and cultural constraints. They were assigned RBQ scores and allotted ranks followed by analysis to reveal crucial insights on the perceived constraints of the cabbage farmers. Under each category, the top ranked constraints were high attack of pests and diseases (RBQ=95) under technical constraints, unavailability of timely credit (RBQ=97.5) under economic constraints, lack of storage facilities (RBQ=99.166) under infrastructural constraints, and difficulty in continuous adoption of traditional methods of   cultivation (RBQ=58.33) under cultural constraints. The suggestions recommended by the farmers were also studied, which included better cold storage facilities (81.6 %), access to timely credit (69.16 %), conducting fortnight meetings at panchayat level to discuss the issues of farmers (60.00 %), provision of inputs at low cost (56.6 %) and conducting more training programmes for farmers (44.16 %). This research highlights the importance of addressing these issues to improve agricultural productivity and farmer livelihoods in the region. Appropriate policy measures should be adopted to strengthen support mechanisms for cabbage farmers in the region.